2016
DOI: 10.1158/2326-6074.cricimteatiaacr15-a160
|View full text |Cite
|
Sign up to set email alerts
|

Abstract A160: Imprime PGG binds to neutrophils through complement, Fc, and dectin-1 receptors, priming these cells for enhanced ROS production and tumor cell cytotoxicity

Abstract: Imprime PGG (Imprime), a soluble yeast 1,3/1,6 β-glucan, is being developed as a novel cancer immunotherapy in conjunction with anti-tumor antibodies in several cancers. In clinical studies, including randomized Phase 2 clinical trials in the 1st-line treatment of stage IV non-small cell lung cancer with bevacizumab, Imprime treatment has shown promising efficacy in both objective tumor response rates and survival. In numerous syngeneic and xenogeneic mouse tumor models, Imprime treatment in combination with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hence, the possibility that ABA level may be prognostic for better responders vs predictive of a BTH1677-specific effect cannot be ruled out. Given the critical role of ABA in facilitating the binding of BTH1677 to immune cells [ 18 22 , 39 42 ] the former seems unlikely; however, controlled studies are needed to further assess the true contribution of ABA in response to BTH1677, as well as to refine the most appropriate ABA thresholds for defining biomarker-positive and biomarker-negative patients in the cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the possibility that ABA level may be prognostic for better responders vs predictive of a BTH1677-specific effect cannot be ruled out. Given the critical role of ABA in facilitating the binding of BTH1677 to immune cells [ 18 22 , 39 42 ] the former seems unlikely; however, controlled studies are needed to further assess the true contribution of ABA in response to BTH1677, as well as to refine the most appropriate ABA thresholds for defining biomarker-positive and biomarker-negative patients in the cancer population.…”
Section: Discussionmentioning
confidence: 99%
“…BTH1677 (Imprime PGG; β(1,6)-[poly-(1,3) -D-glucopyranosyl]-poly-β-(1,3)-Dglucopyranose; Biothera Pharmaceuticals, Inc., MN, USA) is a yeast-derived, water-soluble, 1,3-1,6 β-glucan that functions as a pathogenassociated molecular pattern to drive a coordinated innate and adaptive anticancer immune response in combination with antitumor antibody therapies. BTH1677 initially binds to innate immune effector cells (macrophages, monocytes and neutrophils) through complement receptor 3 and CD32A [11][12][13], activating innate immune cell function and enabling direct killing of antibody-targeted tumor cells [14,15]. BTH1677 also enables re-education of the tumor microenvironment, shifting the normally suppressive M2-state macrophages to a more M1 (tumor attack) state [16,17] and promoting depletion and/or maturation of myeloid-derived suppressor cells in the tumor microenvironment [18].…”
Section: Practice Pointsmentioning
confidence: 99%
“…Imprime PGG is an intravenous formulation of a yeast-derived, uncharged, water-soluble, 1,3–1,6 beta glucan purified from the cell wall of a proprietary, non-recombinant, strain of Saccharomyces cerevisiae . Initial in vitro and animal studies provided insights into bioavailability, pharmacokinetics, pharmacodynamics, ADME, genotoxicity, mutagenicity, safety pharmacology, and general toxicology, information necessary for initiating later clinical trials [ 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. Moreover, ex vivo human whole blood studies demonstrated that Imprime-induced responses were consistent with the innate immune activation elicited by a pathogen.…”
Section: Trained Immunitymentioning
confidence: 99%